Black Rage in New Orleans : Police Brutality and African American Activism from World War II to Hurricane Katrina - Moore, Leonard N., 1971- (Book collections on Project MUSE., 2010)
In Black Rage in New Orleans, Moore traces the shocking history of police corruption in the Crescent City from World War II to Hurricane Katrina and the concurrent rise of a large and energized black opposition to it. Moore explores a staggering array of NOPD abuses - police homicides, sexual violence against women, racial profiling, and complicity in drug deals, prostitution rings, burglaries, protection schemes, and gun smuggling - and the increasingly voceriferous calls for reform by the city's black community. The first book-length study of police brutality and African American protest in.